HISTORY OF THE LANGUAGE DEVELOPMENT STAGES OF THE UZBEK LANGUAGE (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Languages changes over time and their evolution is studied by historical linguistics.The Uzbek language belong to the Turkish language family,holds a prominent position in Central Asia .This article provides an in-depth exploration of the historical development of the Uzbek language,tracing it's evolution from its Turkish roots to it's modern form.The article examines the linguistic significance of Uzbek, including its influences, dialect variations,and its role in shaping the cultural and social identity of Uzbek people.Through a comprehensive analysis of historical records, linguistic studies,and cultural factors ,this article sheds light on the rich history and importance of the Uzbek language